Fabrication of a Novel Implantoplasty Varnish Using Cissus Quadrangularis And Vitex Negundo Formulation Mediated Titanium Dioxide Nanoparticles - Shah, Bhoomi; Rohinikumar, Subhashree; Selvaganesh, Sahana; Thiyaneswaran N, Thiyaneswaran N (Journal of Neonatal Surgery, 2025)
Aims & Background: To fabricate and access the antimicrobial, anti-inflammatory, antioxidant, cytotoxic, and embryonic toxicology properties of a novel implantoplasty varnish using Cissus quadrangularis and Vitex negundo formulation mediated with Titanium dioxide nanoparticles. Materials and methods: The plant extracts of Cissus quadrangularis and Vitex negundo incorporated in Titanium dioxide nanoparticles to synthesize a novel implantoplasty varnish. The varnish was subjected to a variety of tests to assess its antimicrobial, anti-inflammatory, anti-oxidant, cytotoxic, and embryonic toxicology. Further characterization of the nanoparticles was done with UV visible spectroscopy. Results: Nanoparticles inherited important antibacterial properties against Staphylococcus aureus, whereas the zone of inhibition for Enterococcus faecalis and Streptococcus mutans was less. They also possess anti-inflammatory, antioxidant activity and also prove to be biocompatible. It showed no malformation in embryonic toxicology. Conclusion: This novel synthetic implantoplasty varnish may aid in reducing the inflammatory response in the soft tissues surrounding the implant as well as the harmful effects of pathogenic organisms. This can also be helpful in the healing of the soft tissues after implantoplasty is done. Clinical significance: Peri-implantitis is the common reason for bone loss around dental implants for which implantoplasty is the last resort as a treatment choice. The purpose of this study is to lessen plaque adhesion and make it easier to clean the implant surfaces and avoid further bacterial invasion after implantoplasty.